2001
DOI: 10.3201/eid0705.017530
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Discovered Variant of a Hantavirus inApodemus peninsulae, Far Eastern Russia

Abstract: tional PRNT results from 26 sera, of which 18 (69%) were positive, yields a 3.9% positivity rate.In addition to our study, with crude seroprevalence rates ranging from 3.9% to 10.1%, another recent study demonstrated JCV antibodies in 2.9% to 13.3% of ill persons in Massachusetts (Tonry J et al., unpub. data). Although the screening results of our first serosurvey (10.1% positive) differed widely from those of the second serosurvey (3.9% positive), even the lower rate indicates substantial levels of human infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…We detected antibodies to hantaviruses in A. peninsulae , and the viral genome characteristics were extremely similar to the newly identified genotype, AMR (10). Using phylogenetic analysis to characterize the sequences of viruses identified from HFRS patients and A. peninsulae , we were able to corroborate the assumption of Yashina et al (11). We also found that A. peninsulae -related viruses are pathogenic for humans and are distributed over a large area of east Asia that includes Far East Russia.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…We detected antibodies to hantaviruses in A. peninsulae , and the viral genome characteristics were extremely similar to the newly identified genotype, AMR (10). Using phylogenetic analysis to characterize the sequences of viruses identified from HFRS patients and A. peninsulae , we were able to corroborate the assumption of Yashina et al (11). We also found that A. peninsulae -related viruses are pathogenic for humans and are distributed over a large area of east Asia that includes Far East Russia.…”
supporting
confidence: 79%
“…The natural reservoir of AMR genotype seems to be A. peninsulae , according to a recent study on nucleotide sequence comparisons by Yashina et al (11).…”
mentioning
confidence: 99%
“…The few human HFRS cases in Africa [113] and America [115] were not demonstrated to be associated with SEOV, and no clear evidence of SEOV-related HFRS is available in Europe except from laboratory infections [116]. Amur and Far East viruses were recently identified in severe HFRS cases in the far eastern region of the Russia Federation [117,118], and need to be further characterized.…”
Section: Hantaviruses Causing Human Infections Hfrs-associated Hantavmentioning
confidence: 99%
“…SOO virus sequences from four Vero E6 cell-culture isolates were aligned and compared with previously published hantavirus sequences [Liang et al, 1994;Baek et al, 1998;Yashina et al, 2000Yashina et al, , 2001, using the Clustal W method (Lasergene program version 5, DNASTAR, Inc., Madison, WI). The GenBank accession numbers for the S segment of SOO virus strains SOO-1, SOO-2, SOO-3, and SOO-4 were AY675349, AY675350, AY675351, and AY675352; for the M segment of strains SOO-1, SOO-2, and SOO-3, they were AY675353, DQ056293, and DQ056295; and for the L segment of strains SOO-1 and SOO-2, they were DQ056292 and AY675354, respectively.…”
Section: Phylogenetic Analysismentioning
confidence: 99%